State of glucocorticoid function and its regulation in patients with laryngeal cancer depending on the stage of the disease - V. V. Kalyi; N. A. Chertova (Бюллетень сибирской медицины, 2010)
Glucocorticoid supply of the organism of patients with laryngeal cancer at different stages of malignant process has been studied. Formation and development of laryngeal cancer is accompanied by hormone-metabolic disturbances of hypophysis-adrenalocortical system, their character and degree of development being determined to a large extent by the stage of malignant process.